Synthesis and biological evaluation of N-arylpiperazine derivatives of 4,4-dimethylisoquinoline-1,3(2H,4H)-dione as potential antiplatelet agents - Monika Marcinkowska; Magdalena Kotańska; Agnieszka Zagórska; Joanna Śniecikowska; Monika Kubacka; Agata Siwek; Adam Bucki; Maciej Pawłowski; Marek Bednarski; Jacek Sapa; Małgorzata Starek; Monika Dąbrowska; et al. (Taylor & Francis Group, 2018)
Despite the substantial clinical success of aspirin and clopidogrel in secondary prevention of ischemic stroke, up to 40% of patients remain resistant to the available antiplatelet treatment. Therefore, there is an urgent clinical need to develop novel antiplatelet agents with a novel mechanism of action. Recent studies revealed that potent alpha 2B-adrenergic receptor (alpha 2B-ARs) antagonists could constitute alternative antiplatelet therapy. We have synthesized a series of N-arylpiperazine derivatives of 4,4-dimethylisoquinoline-1,3(2H,4H)-dione as potential alpha 2B receptor antagonists. The most potent compound 3, effectively inhibited the platelet-aggregation induced both by collagen and ADP/adrenaline with IC50 of 26.9 μM and 20.5 μM respectively. Our study confirmed that the alpha 2B-AR antagonists remain an interesting target for the development of novel antiplatelet agents with an alternative mechanism of action.